Modeling & simulation of micro reactor with nitration of 2-methyl-4,6 dihydroxy-pyrimidine - Mandal, Alok Kumar; Pandey, Raj Kishore; Asthana, Nandan; Kulkarni, Amol; Kulkarni, Bhaskar Dattatraya (Science and Technology of Energetic Materials, 2011)
Nitration of 2-methyl-4,6-dihydroxypyrimidine (MDP) using concentrated sulfuric acid and nitric acid as nitrating mixture is a highly exothermic and hazardous reaction. Conducting such reaction in a batch reactor follow an unsteady state and its trajectory depends on various important parameters such as initial reactor temperature, initial composition of reaction mass, temperature of circulating coolant, etc. However, over all productivity, process control and safety of the batch process is highly restricted due to lower surface to volume ratio. In the present work, an effort has been made to over come the limitations of batch reactor by using the novel micro reactor device. Micro reactor is having extremely high surface to volume ratio, which has been explored to carry out nitration of MDP both numerically as well as experimentally and the results were compared with conventional batch reactor. The micro reaction system has been modeled using two dimensional (2-D) heat flow and mass transfer equations. The kinetic rate equation for nitration of MDP has evaluated experimentally by differential method which is used in modeling of the micro reactor. The numerical results from the 2-D model for conversion and temperature profile along the length and radius of micro reactor have been compared with corresponding results obtained from batch reactor. In order to validate the model, several experiments were conducted in micro reactor set-up with the variation of flow rate, residence time, concentration, temperature, etc. The experimental results from micro reactor revealed that nitration of MDP takes place even at much lower concentration and lower residence time with better control of temperature profile. Also, the reaction takes place in laminar region compared to turbulent region in corresponding batch reactor setup.
Keywords: 2-D modeling; 2-methyl-4; 6 dihydroxypyrimidine; Batch reactor; micro reactor

Large centimeter-sized macroporous ferritin gels as versatile nanoreactors - Kumari, Sushma; Kulkarni, Amol; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Chemistry of Materials, 2013)
Organized assemblies of bionanoparticles such as ferritin provides templates that can be exploited for nanotechnological applications. Organization of ferritin into well-defined three-dimensional assemblies is challenging and has attracted considerable attention recently. We have synthesized, for the first time, large (centimeter-sized) self-standing macroporous scaffold monoliths from ferritin bionanoparticles, using dynamic templating of surfactant H-1 domains. These scaffolds comprise three-dimensionally connected strands of ferritin, organized as a porous gel with porosity similar to 55 mu m. The iron oxide inside the ferritin scaffold can be easily replaced with catalytically active monodisperse zerovalent transition metal nanoparticles using a very simple protocol. Since the ferritin is cross-linked in the scaffold, it is significantly robust with enhanced thermal stability and better tolerance toward several organic solvents in Comparison to the native ferritin bionanoparticle. In addition, the scaffold macropores facilitate substrate and reagent transport and hence the monoliths containing active Pd or iron oxide nanoparticles inside apo-ferritin bionanoparticles were used as a recyclable heterogeneous catalyst for the oxidation of 2,3,6-trimethyl phenol to 2,3,6-trimethyl-1,4-benzoquinone (precursor for Vitamin E synthesis) and for Suzuki-Miyaura cross-coupling reaction in both aqueous and organic solvents. The protein shell around the nanoparticles protects them from agglomeration, a phenomenon that otherwise plagues nanoparticles-based catalysis. The presence of macropores allow the ferritin scaffold to act as catalytic monolith for continuous flow reactions having rapid reaction rates, while offering a low pressure drop. Finally, the Pd@apo-ferritin scaffold was immobilized inside a steel cartridge and used for the continuous flow hydrogenation of alkenes to their corresponding alkanes for 15 cycles without any loss of activity.
Keywords: catalysis; continuous flow; ferritin; gel; macroporous materials; Self-assembly

Microreactor-based continuous process for controlled synthesis of poly-methyl-methacrylate-methacrylic acid (PMMA) nanoparticles - Dobhal, Anurag; Kulkarni, Amol; Dandekar, Prajakta; Jain, Ratnesh (Journal of Materials Chemistry B, 2017)
We have developed a microreactor-based continuous process for synthesizing PMMA nanoparticles (NPs), based on the principle of nanoprecipitation. Our objective was to identify the critical parameters governing the size of nanoparticles, produced in microreactors, to enable reproducible synthesis of mono-disperse particles. Experiments were carried out in a microreactor, where parameters like flow rates of aqueous and organic phases, residence time and polymer concentrations were varied to examine their influence on particle size and homogeneity. The results from Dynamic Light Scattering confirmed that the particle size decreased with decreasing residence time, whereas when the aqueous to organic phase flow rate ratio was changed sequentially from 9 : 1, 4 : 1, 7 : 3, 3 : 2, to 1 : 1 (v/v), the particle size increased. Particles fabricated using a microreactor demonstrated a narrow and homogenous distribution, thus confirming their monodispersity. TEM, SEM and XRD were also performed for morphology analysis and phase identification of the particles. Further, paclitaxel encapsulated PMMA nanoparticles were prepared using the microreactor, demonstrating an increase in mean size of around 30 nm and a slightly higher polydispersity index compared to the blank nanoparticles. The drug encapsulation efficiency and drug release kinetics of these nanoparticles were comparable to those prepared in batch-experiments, thus establishing the suitability of the technology for preparing drug-loaded nanoparticles. Also, it was observed that at all the residence times (10 min to 10 s), about 80% of the polymer got transformed into nanoparticulate form, thus confirming the efficiency of the microreactor. In recent times, much work has been conducted to synthesize polymeric nanoparticles using different types of microreactors, but they lack detailed investigation of the effect of various parameters on the physiochemical properties of the resulting particles. Our investigation synthesizes PMMA NPs, using microreactor technology, for the very first time, to the best of our knowledge. Furthermore, we have performed a detailed analysis of the influence of various process parameters on the size and uniformity of the resulting nanoparticles. These critical parameters can serve as a useful tool to synthesize a myriad of nanoparticles of alternative polymers, using microreactor technology.

Continuous flow synthesis of micron size silica nanoparticles: parametric study and effect of dosing strategy - Jundale, Rajashri; Bari, Atul; Thara, Chinnu; Kulkarni, Amol (Journal of Flow Chemistry, 2018)
This work for the first time reports continuous flow synthesis of silica nano-particles of size over 1 mu m using a simple tubular reactor. The systematic approach involves the study of effect of various parameters like: ammonia concentration, water concentration, electrolyte concentraton, temperature, solvent, residence time and mode of TEOS injection over a wide range. A combination of ethanol and butanol was used as the medium with relatively lower polarity. Various process parameters were optimized to obtain highly monodispersed particles of size up to 600 nm and high yield (up to 90%). Attempts of reducing the reaction time by increasing temperature or concentrations of any of the reagents resulted in significant polydispersity and even in the formation of random shape agglomerates. At the optimized conditions almost complete conversion of TEOS happenned within 40 min and further growth of particles was achieved by adding TEOS using multipoint injection approach. While multipoint dosing resulted in the formation of very small number of secondary particles, the larger particles continued to grow beyond 800 nm. Further reduction in the polarity of reaction medium was achieved by adding 20% v/v of toluene, which without changing homogeneity of the solution resulted in particles as large as 0.9-1.1 mu m.
Keywords: Flow synthesis; Multipoint injection; silica; TEOS; Tubular reactor

Modulation of reactivity of singlet radical pair in continuous flow: photo-fries rearrangement - Karjule, Neeta; Sharma, Mrityunjay K.; Nithyanandhan, Jayaraj; Kulkarni, Amol (Journal of Photochemistry and Photobiology A: Chemistry, 2018)
Photo-Fries rearrangement of phenyl benzoate is studied using continuous flow for modulating the reactivity of singlet radical pair by changing the viscosity of the solvent. The effect of flow and proximity of the reactants with the light source on the reactivity of radical pair, formed from singlet excited state was investigated in details. In non-viscous solvent, the results from flow synthesis were comparable to batch reactor. In viscous solvents, selectivity of ortho- and para-isomers (o-/p- isomer) of the product could be controlled by changing viscosity as well as the flow rate. Using flow synthesis, ortho- and para-isomer ratio was obtained as high as 8.45 which are twice as compared to batch experiment with in fraction of residence time.

Editorial special issue in the journal of flow chemistry: engineering aspects of flow chemistry - Kockmann, Norbert; Hartman, Ryan; Kulkarni, Amol (Journal of Flow Chemistry, 2021)

Direct (hetero)arylation (DHAP) polymerization of conjugated polymers - new A-B-A monomer design for P(NDI2OD-T2) & the challenges of adopting DHAP for continuous flow processes - Kakde, Navnath R.; Bharathkumar, H. J.; Wavhal, Bhaiyyasaheb A.; Nikam, Arun; Patil, Suneha; Dash, Soumya Ranjan; Vanka, Kumar; Krishnamoorthy, K.; Kulkarni, Amol; Asha, S. K. (Journal of Materials Chemistry C, 2022)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, was synthesized by the atom-economic direct hetero arylation polymerization (DHAP) route using a newly designed A-B-A monomer. The new monomer design involved flanking naphthalene diimide with bithiophene units in the bay position, which was further polymerized with bay substituted 1,4-dibromo naphthalene diimide, to afford the same polymer structure as P(NDI2OD-T2). The new monomer design resulted in a very high molecular weight (M-n: 99.5 kDa, D-M: 2.8) defect-free polymer in a quantitative yield by the DHAP batch process using 1,2,4-trichlorobenzene (TCB) as the solvent. DFT studies revealed that the abstraction of the alpha-proton from the naphthalene diimide substituted 2,2 `-bithiophene was favorable by 2.6 kcal mol(-1) (Delta Delta G) as compared to that from 2,2 `-bithiophene. The reason for this improved C-H activation at the alpha position can be attributed to the presence of C-HMIDLINE HORIZONTAL ELLIPSIS pi stabilizing interactions in naphthalene diimide substituted 2,2 `-bithiophene, which strengthens upon the extended charge delocalization throughout the ring, thus stabilizing the conjugate base generated after the proton abstraction. Continuous flow polymerization was carried out by pumping the DHAP reaction mixture including the monomers, catalyst, and additive (pivalic acid) solubilized in degassed TCB through a pre-heated glass condenser packed with K2CO3 and Celite under aerobic conditions. Reproducible molecular weights of M-n: 29.5 kDa, D-M: 1.7 were obtained at much lower concentrations of reactant mixture compared to that for batch polymerization. This is the first report of the synthesis of P(NDI2OD-T2) by a Continuous Flow Process adopting the DHAP route to obtain a defect-free polymer with reasonable molecular weights. P(NDI2OD-T2) was also synthesized by Stille polymerization as a reference control sample to compare the thermal and charge carrier transport properties of the DHAP polymers. Organic field-effect (OFET) mobility measurements indicated mobility values in the order of 10(-3) cm(2) V-1 s(-1) for the DHAP batch polymer (using the novel monomer design). The P(NDI2OD-T2) synthesized by DHAP batch using the commonly used starting materials - bisbromo naphthalene diimide and bithiophene, exhibited OFET mobilities which were one order less, similar to 10(-4) cm(2) V-1 s(-1). This observation highlights the importance of structural design in the monomer to enhance reactivity and thereby the bulk properties using the DHAP route.